1999
DOI: 10.1103/physreva.59.r4117
|View full text |Cite
|
Sign up to set email alerts
|

Complete view of Stark wave-packet evolution

Abstract: Picosecond laser pulses have been used to produce Rydberg wave packets in calcium atoms in the presence of a strong static electric field. The dynamics of the Stark wave packets have been observed by measuring the momentum-space probability distribution as a function of time. The full precession of the electronic orbital angular momentum, the appearance of a large-amplitude, linear oscillation of the electronic dipole moment, and a pronounced, periodic up-down asymmetry in the momentum distribution are all obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…It has experimentally been demonstrated that an ionization probability of 10% of an ensemble of Rydberg atoms scales as F 10% ‫ق‬ 1 n 2 , while a 50% ionization probability scales as F 50% ‫ق‬ 1 n 3͞2 [1,2]. A HCP also appeared to be a good tool to design and manipulate Rydberg wave packets [3] and give a time dependent view of a wave packet [4]. Also a HCP can be used to study weakly bound Rydberg electrons [5].…”
mentioning
confidence: 99%
“…It has experimentally been demonstrated that an ionization probability of 10% of an ensemble of Rydberg atoms scales as F 10% ‫ق‬ 1 n 2 , while a 50% ionization probability scales as F 50% ‫ق‬ 1 n 3͞2 [1,2]. A HCP also appeared to be a good tool to design and manipulate Rydberg wave packets [3] and give a time dependent view of a wave packet [4]. Also a HCP can be used to study weakly bound Rydberg electrons [5].…”
mentioning
confidence: 99%
“…An HCP acting on an electronic wave packet changes the electron energy depending on its instantaneous linear momentum along the direction of the HCP. This feature has enabled experiments in the past that have used directed HCP's to map the time-resolved momentum distribution of the electron in its orbit [13,14]. When the Stark wave packet evolves to high angular momentum, the corresponding classical orbits of the electron are along the lines of constant longitude on the surface of a sphere where the poles are aligned in the direction of the electric field.…”
Section: Discussionmentioning
confidence: 99%
“…Several detection methods have been used with varying degrees of success, for example, short pulse pump-probe ionization [9], bound statestate interferometry [10], and time-resolved streak camera detection of ionization [11]. Detection of Stark wave packet dynamics has also been successfully demonstrated using HCP's [12,13,14]. In those previous experiments, the detection relies on the fact that an HCP induces a change of electron's total energy, ∆E = p • Q + Q 2 /2, to ionize the electrons.…”
Section: Introductionmentioning
confidence: 99%
“…The nearly macroscopic size of highly excited Rydberg atoms has inspired a variety of experiments that explore quantum-classical correspondence. These include excitation of wavepackets with varying degrees of localization [1][2][3][4][5][6], creation of a Schrödinger cat-like state [7,8], and studies in combined electric and magnetic fields, where an equivalent classical system would exhibit chaos [9][10][11][12]. The large coupling between neighboring Rydberg states allows pairs of atoms to exchange energy in a dipole-dipole interaction [13].…”
Section: Introductionmentioning
confidence: 99%